(untitled) (Journal of Science and Technology, 2016)
Between January 4 July 1990 all admissions to the adult medical wards of the Komfo Anokye Teaching Hospital, Kumasi, Ghana were studied. Among 2431 consecutive admissions, the prevalence of hypertension was 14.39%. Hypertension was found to be commonest in the age group 55.64 (26.86%). Stroke (CVA) was the most common complication of hypertension with 37.71%, followed by congestive cardiac ’failure with 15.14%. Myocardial infarction was rare accounting for 0.28%. Hypertension was often associated with Diabetes mellitus in 4.28%. It was observed that all the patients with chronic uraemia were hypertensive. They could not be adequately treated in our present medical set up.